Mewujudkan Sustainable Development Goals (SDGS) Tentang Penyediaan Air Bersih dan Sanitasi - Oktafiani, Annisa Isni; Nugraheni, Nursiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The availability of clean water and sanitation is a very important aspect for society because its presence is essential in various daily activities, so its quality must be prioritized. However, in reality this is still not fully fulfilled and contributes to public health problems. Therefore, this research was conducted to investigate problems related to the provision of clean water and sanitation in the context of sustainable development, as well as ways to overcome these challenges. The method used in this research is qualitative, by collecting primary data through literature studies from various sources such as books, scientific journals, articles, the internet and other literature. Researchers will conduct a systematic review of several recent journals published between 2019 and 2024, to be used as references in developing teaching materials. Efforts to overcome clean water and sanitation problems are part of achieving the Sustainable Development Goals (SDGs), which then become the basis for implementing national targets related to clean water and sanitation.